Hammermill as a tool to unshell rubber seeds - Hardjosuwito Baryono; Hermansyah
To extract oil rubber seed kernels first pf all dried rubber seed shells were crushed. Manual decortication consumed too much time and needed a high labour cost. A hammermill consisting of 72 hammers made of rubber with specific properties and a screen with 10 slits, wherein the size of each slit's aperture and the opening of feeder are respectively 2.0 x 21.0 cm and 3.0 x 21.0 cm, produced unshelled seeds with a fair quality and a good economic value. To improve the practical separation of kernels from rubber seed shells and unshelled seeds, a wire case sieve with an aperture of 1.1 x 1.1 cm and a total size of 35.0 x 85.0 cm had been utilized. This hammermill runned on a 1 hp electrical motor with a capacity of about 462 kg of rubber seeds per hour, and only 6.8;seeds were left unshelled.
Keywords: Hammermill; Rubber seed kernel; Rubber seeds